Microwave hydrothermal sulfidation process for zinc-containing plating sludge. Issue 17 (22nd November 2021) - Tan, Hao; Jin, Junxun; Shao, Yuchao; Zhou, Dan; Zhou, Ying; Wu, Zixiao; Wu, Minjin; Shen, Dongsheng; Long, Yuyang
ABSTRACT: The present study describes the conversion of zinc into a sulfide-containing plating sludge via a microwave hydrothermal sulfidation (MHS) process for use in heavy metal remediation by flotation. The research herein focused on circumventing the operational issues of traditional hydrothermal sulfidation (THS) at high temperature and high pressure. The following optimized process conditions of temperature 153°C, reaction time 63 min, liquid-to-solid ratio 16:1 and S 2− concentration 49% were obtained using a single-factor test and the Box–Behnken design test, to yield a maximum sulfidation ratio of 92.90%. Moreover, the economic analysis shows the superiority of the MHS process. Graphical Abstract: uf0001